Quantitative microbial risk assessment: Research status and future development - Hung Nguyen-Viet; Nguyen, H.N.; Nguyen, T.B.T.; Haas, C.N. (2012)
Quantitative Microbial Risk Assessment (QMRA) is much more developed and applied in developed countries than in developing world although risk assessment of pathogen exposure is increased in developing countries due to the unhygienic condition and (re)emerging infectious diseases. However, QMRA needs further methodological development to improve its usefulness. We argue that promoting the use and development of QMRA in developing countries and identifying its methodological gaps to be filled in future are needed. This paper aims to have an overview on the usage of this method in scientific community worldwide and discuss possible directions for the application and research of QMRA. We systematically searched peer-reviewed publication on QMRA from until December 2011. We found 463 papers related to QMRA but the majority of these (91%) were published in the 2000s. Only 3.5% of the papers were published by authors from developing countries, meaning that this method is developed and extensively used in developed world, in particular US, Europe and Australia. QMRA has been applied mainly in the domain of food (54.2%) and water (9.5%, mostly for drinking water) and less focused on sanitation (6.5%), waste and recreational water and others. The number of studies on dose-response assessment increases, whereas information on exposure assessment is limited and relies mainly on assumption. Application of statistics and integration of parameters such as exposure time, age and immunity of the host into the dose-response model is observed. However, dose-response models need to be developed for other remaining pathogens, in particular new emerging infectious diseases and further studies on exposures needed. Researchers from developing countries would need to be more proactive in using and developing QMRA in partnership with experienced researchers from developed countries.